Noni simplistic effect with Chicken Shank Gelatin Film on White Rat Spleen Exposed to Dexamethasone - Pratiwi, Virita Rossa; Kuntana, Yasmi Purnamasari; Budiono, Ruly; Malini, Desak Made; Kusmoro, Joko (Jurnal Veteriner; Vol 24 No 1 (2023), 2023)
Dexamethasone is a corticosteroid drug belong to glucocorticoid group. Dexamethasone is immunosuppressant and anti-inflammatory in various inflammatory conditions. Side effects of its use can cause cell apoptosis in various organs such as the spleen. The immunosuppressant effect of dexamethasone can reduce and inhibit peripheral lymphocytes and macrophages until the death of lymphoid cells in the white pulps of the spleen. The simultaneous effect of administering chicken shank gelatin and noni has the potential to improve the structure of the spleen. This study was aimed to prove and obtain effective and safe dose of chicken shank gelatin and noni on the spleens of rats exposed to dexamethasone. The research was carried out experimentally in the laboratory with a completely randomized design (CRD). A total of 25 heads male rats were grouped into five treatments and each treatment consist of five repetitions. There was a treatment group P1 as a negative control, P2 as a positive control (dexamethasone 5 mg/kg BW), P3-P5 (dexamethasone 5 mg/kg + gelatin 1.585 mg/kg + noni simplicia 50; 112; 250 mg/kg BW). The results of the study showed an increase in the area of white pulps and a decrease in the percentage of necrotic cells in the spleen, however, it did not increase the relative weight of the spleen and serum albumin levels (P>0.05). In conclusion, the effective and safe dose for the spleen organs of rats exposed to dexamethasone is 250 mg/kg BW.